PENGARUH PENEMPATAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PT. TUNAS DWIPA MATRA CABANG MARTAPURA OKU TIMUR - Tutut Anggun Tamara; Noviansyah Noviansyah; Muznah Muznah (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2022)
ABSTRACT The data analysis technique used was Multiple Linear Regression. Based on the results of the partial analysis there was a significant influence of work placement on the performance of employees at PT. Tunas Dwipa Matra Martapura Branch, East OKU with a t-value of 3,201. Organizational commitment variable had a significant influence on the performance of PT. Tunas Dwipa Matra Martapura Branch, East OKU with a t-value of 2.616. Simultaneously, it was found that there was an influence of work placement and organizational commitment on the employees’ performance at PT. Tunas Dwipa Matra Martapura Branch, East OKU with an F count of 19,573. The coefficient of determination (R2) obtained was 0.583. This shows that the contribution of the influence of work placement and organizational commitment to the performance of employees at PT. Tunas Dwipa Matra Martapura Branch, East OKU by 58.3% while the remaining 41.7% was influenced by other variables not included in this study, for example ability and expertise, knowledge, work design, personality, work motivation, leadership, leadership style, organizational culture, job satisfaction, work environment, loyalty, and work discipline (Kasmir, 2016: 189).